Ward Atmosphere and Patient Satisfaction in Psychiatric Hospitals With Different Ward Settings and Door Policies. Results From a Mixed Methods Study - Efkemann, Simone Agnes; Bernard, Johannes; Kalagi, Janice; Otte, Ina; Ueberberg, Bianca; Assion, Hans-Jörg; Zeiß, Swantje; Nyhuis, Peter W.; Vollmann, Jochen; Juckel, Georg; Gather, Jakov (Frontiers in Psychiatry, 2019)
Background: Open-door policies in psychiatry are discussed as a means to improve the treatment of involuntarily committed patients in various aspects. Current research on open-door policies focuses mainly on objective effects, such as the number of coercive interventions or serious incidents. The aim of the present study was to investigate more subjective perceptions of different psychiatric inpatient settings with different door policies by analyzing ward atmosphere and patient satisfaction. Methods: Quantitative data on the ward atmosphere using the Essen Climate Evaluation Scale (EssenCES) and on patient satisfaction (ZUF-8) were obtained from involuntarily committed patients (n = 81) in three psychiatric hospitals with different ward settings and door policies (open, facultative locked, locked). Furthermore, qualitative interviews with each of 15 patients, nurses, and psychiatrists were conducted in one psychiatric hospital with a facultative locked ward comparing treatment in an open vs. a locked setting. Results: Involuntarily committed patients rated the EssenCES’ subscale “Experienced Safety” higher in an open setting compared with a facultative locked and a locked setting. The subscale “Therapeutic Hold” was rated higher in an open setting than a locked setting. Regarding the safety experienced from a mental health professionals’ perspective, the qualitative interviews further revealed advantages and disadvantages of door locking in specific situations, such as short-term de-escalation vs. increased tension. Patient satisfaction did not differ between the hospitals but correlated weakly with the EssenCES’ subscale “Therapeutic Hold.” Conclusion: Important aspects of the ward atmosphere seem to be improved in an open vs. a locked setting, whereas patient satisfaction does not seem to be influenced by the door status in the specific population of patients under involuntary commitment. The ward atmosphere turned out to be more sensitive to differences between psychiatric inpatient settings with different door policies. It can contribute to a broader assessment by including subjective perceptions by those who are affected directly by involuntary commitments. Regarding patient satisfaction under involuntary commitment, further research is needed to clarify both the relevance of the concept and its appropriate measurement.